Non-acceptance of permanent methods of contraception-a threat to small family norm: a cross-sectional study from the Northern state of India - Singh, Rajesh Kumar; Kaur, Amandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: India is second most populous country of the world after China and is expected to surpass China by 2024. In order to balance the population growth, replacement-level fertility – total fertility rate of 2.1 – needs to be achieved and sustained even at sub-national level. Acceptance of permanent family planning methods by young couples can be an effective way of eliminating risk of future pregnancies. The objective of the present study was to assess acceptance and determinants of acceptance of permanent methods of contraception among couples with two or more living children. Methods: A community based cross-sectional study was conducted during September 2017-April 2018 in Haldwani block of Nainital District of Uttarakhand, India. The study participants were selected by multi-stage sampling and were interviewed using semi-structured and pretested questionnaire. The statistical analysis was done using the software R. Chi-square test was used to test association between variables. Results: Among 221 interviewed study subjects, only 34.39% were using permanent method of contraception and out of these, 96.05% were acceptors of tubectomy while only 3.95% preferred vasectomy. One in four couples were not using any contraceptive method and rest chose temporary contraceptive techniques. Non-acceptors were especially high in case of couples with women belonging to lower age-group, living in joint families, having only one or no male child and with formal schooling. Conclusions: Non-acceptance of permanent method of contraception for limiting the family after two children was very high in the community and desire for male child being its important determinant.